Introduction, Transmission Dynamics, and Fate of Early Severe Acute Respiratory Syndrome Coronavirus 2 Lineages in Santa Clara County, California. (20th April 2021) - Villarino, Elsa; Deng, Xianding; Kemper, Carol A; Jorden, Michelle A; Bonin, Brandon; Rudman, Sarah L; Han, George S; Yu, Guixia; Wang, Candace; Federman, Scot; Bushnell, Brian; ,; et al.
Abstract: We combined viral genome sequencing with contact tracing to investigate introduction and evolution of severe acute respiratory syndrome coronavirus 2 lineages in Santa Clara County, California, from 27 January to 21 March 2020. From 558 persons with coronavirus disease 2019, 101 genomes from 143 available clinical samples comprised 17 lineages, including SCC1 (n = 41), WA1 (n = 9; including the first 2 reported deaths in the United States, with postmortem diagnosis), D614G (n = 4), ancestral Wuhan Hu-1 (n = 21), and 13 others (n = 26). Public health intervention may have curtailed the persistence of lineages that appeared transiently during February and March. By August, only D614G lineages introduced after 21 March were circulating in Santa Clara County. Abstract : We used viral whole-genome sequencing with contact tracing to investigate the introduction, transmission, and fate of 17 severe acute respiratory syndrome coronavirus 2 lineages into Santa Clara County, California, early in the pandemic in the United States (January–March 2020).